Surimi Powder Inclusion with Semolina-based Pasta Product– A Potential Method of Protein Fortification - Ikbal, Asik; Chowdhury, Supratim; Murmu, Prasanta; Dora, K. C.; Nath, Swarnadyuti; Roy, Sayani; Saklani, Pooja (International Journal of Bio-resource and Stress Management, 2022)
Starch-based foods are the rich source of carbohydrates with a high glycaemic index and lack of essential amino acids as well as essential fatty acids causing unhealthy attributes. Thus, these are nutritionally imbalanced foods. As demand for convenience, nutritionally balanced foods are gradually increased in many developing countries, the cereal industries have also taken the challenge to provide healthier food with increased shelf life. Fish and fisheries products are a good source of polyunsaturated fatty acids (mainly docosahexaenoic acid and eicosapentaenoic acid), essential amino acids (particularly methionine, lysine, histidine, etc.), important vitamins (A, D, B6, and B12), and minerals (iron, zinc, iodine, selenium, potassium, and sodium), making it a global highly traded commodity with an average per capita consumption of 20.5 kg worldwide. In the meantime, semolina-based pasta is highly popular in some Asian as well as western countries because of its low cost, ease of preparation, and saving much time. Market demand for such products is increasing day by day because of industrialization and the need for diversified ready-to-serve or instant ready products in so-called busy societies. Pasta is a very popular food product in China, Korea, Japan, USA, India because of its’ versatility, low cost, ease of preparation. Thereafter, adding values by fortification of healthy nutrients according to consumers’ preference, it will also be triggered with high market value in terms of nutritional quality. With this view, cereal products can be fortified with protein as well as lipid-rich constituents such as surimi powder or fish protein powder.